'A Punch Has No Paternity!': techniques, belonging and the Mexicanidad of Xilam. (September 2021) - Jennings, George
This article combines ethnographic and netnographic data to explore the relationships between body techniques and a sense of belonging through the contemporary Mexican martial art of Xilam . This art, founded by a female Mexican martial arts veteran, is slowly developing as a hand-to-hand sport, and has attracted critics for its supposed use of East Asian fighting techniques. Netnographic data reveal online debates on the origins and 'true belonging' of specific techniques while ethnographic fieldwork in a Xilam school demonstrates how the art is made 'Mexican' through specific accompanying practices and philosophy surrounding the movements. The movements of sitting, punching and standing are selected as key examples as understood through Mauss's classic thesis. I conclude that Xilam follows a philosophical pedagogy that associates these techniques with a sense of Mexicanness – Mexicanidad.